A case study of using 7S framework to improve business process for call centre reforming. (1st January 2012) - Hsu, C.F.; Peng, C.H.
Call centre is the core of building customer relationship management system. Under the strong competitive stress, it becomes a new profiting challenge for a successful organisation. Call centre is a department not only to provide customer service but also to bring business benefit. This is the qualitative case study in Taiwan bank service industry which goes on deeper exploration, and analysis by business interviews and industrial analysis. This study starts from the establishment, development, and management after the reforming of the case call centre. This study adopted 7S framework to improve the call centre reforming process that explains how the call centre reforms from service-oriented to profit-oriented and from cost management to profit management. The result demonstrated how 7S framework improving on the call centre reforming process that is operated as a market profit competition centre. The conclusion is indicated to support the call centre on marketing profit by research analysis result.